Upaya Mengembangkan Keterampilan Motorik Halus Anak Melalui Pemanfaatan Media Pengolahan Bahan Bekas Koran Pada Anak Kelompok B1 Tk Arsy Kec.Gisting Kab.Tanggamus - Nurul Fitriani (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2026)
Based on the identification results, there is a lack of children's fine motor skills, so in this research what will be developed is children's fine motor skills. This research was carried out at the AT-TAQWA TETA Kindergarten, Lambitu District, 2023/2024 academic year with the aim of improving learning in early childhood group B to improve fine motor skills through collage activities with various media. This research was carried out using classroom action research which was carried out in two cycles, namely cycle I and cycle II which began with learning planning activities then implementing learning and reflection. The results obtained from this learning improvement research from cycle I of the research show that the use of varied media in collage activities contributes significantly to improving children's fine motor skills. In cycle I, children's fine motor skills showed an increase of 60%. Through reflection and adjustment, in cycle II, there was a further increase, reaching 80%. This reflects the positive impact of using varied media in collage activities on children's fine motor development. This research confirms that collage activities with varied media are effective in improving children's fine motor skills. These results contribute to our understanding of the importance of structured and creative arts activities in the development of fine motor skills in early childhood. The implications of these findings can be a reference for teachers and educators to design more effective learning strategies in the context of children's fine motor development at the early childhood education level